1994
DOI: 10.1007/bf00178846
|View full text |Cite
|
Sign up to set email alerts
|

A model for the correlation of mutation rate with GC content and the origin of GC-rich isochores

Abstract: Based on the biochemical kinetics of DNA replication and mutagenesis, including misincorporation and correction, a model has been developed for studying the relationships among the mutation rate (u), the G+C content of the sequence (f), and the G+C proportion in the nucleotide precursor pool (N). Also a measure for the next-nucleotide effect, called the maximum capacity of the next-nucleotide effect (MC), has been proposed. Under the normal physiological conditions of mammalian germ cells, our results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…and differences in the timing of replication in S-phase (Wolfe 1991;Gu and Li 1994) are potentially quite complex and cannot be resolved with this type of data. However, future examination of intranuclear localization, including proximity to matrix attachment sites, pericentromeric heterochromatin, the nuclear membrane, and sites of chiasmata during meiosis may show significant correlations with divergence.…”
Section: Variation In Evolutionary Ratesmentioning
confidence: 99%
“…and differences in the timing of replication in S-phase (Wolfe 1991;Gu and Li 1994) are potentially quite complex and cannot be resolved with this type of data. However, future examination of intranuclear localization, including proximity to matrix attachment sites, pericentromeric heterochromatin, the nuclear membrane, and sites of chiasmata during meiosis may show significant correlations with divergence.…”
Section: Variation In Evolutionary Ratesmentioning
confidence: 99%
“…Pioneering studies suggested that changes in nucleotide pools during replication could be responsible for mutation rate fluctuations (Wolfe et al 1989;Gu and Li 1994), because different genomic regions replicate at different times during the S phase (MacAlpine et al 2004;Woodfine et al 2004;Karnani et al 2007;Hiratani et al 2008). Studies of limited portions of the human genome confirmed that mutation rates increase in late-replicating regions (Watanabe et al 2002;Stamatoyannopoulos et al 2009).…”
mentioning
confidence: 99%
“…They found the existence of strong long-range correlations in noncoding regimes, and weaker long-range correlations in coding regimes in excellent agreement with [49]. More recently, they found that the correlations in coding DNA are restricted to the third degenerate nucleotide of the codon [67], which may be related to the presence of the isochores, i.e., long regions of high or low C+G content [68].…”
Section: Systematic Analysis Of Genbank Databasementioning
confidence: 92%
“…[64,65]). These patches may represent di erent structural elements of 3D chromosome organization, e.g., the DNA double helix with period 10.5 bp [66] nucleosomes about 200 bp long, 30 nm ÿber, looped domains of about 10 5 bp, and chromatin bands [67,68] or isochores that may consist of several million nucleotides. Such hierarchical structure of several length scales may produce e ective long-range power-law correlations.…”
Section: Detrended Uctuation Analysis (Dfa)mentioning
confidence: 99%
See 1 more Smart Citation